Implementation of Differentiated Learning with Project Based Learning Model to Increase Students' Interest and Learning Outcomes on Molecular Structure Material - Sunartri, Sunartri (Universitas Islam Indonesia, 2025)
This is a Classroom Action Research (CAR) that aims to increase students' interest and learning outcomes in class XI chemistry material, which is the structure of molecules, at SMA Negeri 1 Cangkringan, Sleman, Yogyakarta. with a total of 34 students. Differentiated learning was used alongside a project-based learning model to conduct learning activities. This research began with pre-cycle activities to collect data on student profiles for mapping differentiated learning based on students' learning styles and initial abilities. Furthermore, the data collected was used to conduct classroom action research in two cycles. Each cycle consists of several stages, including planning, action implementation, observation, and reflection. To obtain data on the study's findings, data collection was conducted qualitatively and quantitatively for students' interests and learning outcomes. The findings revealed that by implementing differentiated learning through the project-based learning model, students' learning outcomes improved from 74% classical completeness in cycle 1 to 95% in cycle 2. In the cycle 1, 74% of students achieved the minimum competency standards and in the cycle 2 it increased to 95%. Students' interest in learning increased in all indicators from cycle 1 and improved even more in cycle 2. As a result, it is possible to conclude that the use of differentiated learning in conjunction with a project-based learning model can increase the interest and learning outcomes of chemistry students in class XI MIPA 1 SMA Negeri 1 Cangkringan during the 2023/2024 academic year on molecular structure materials.